Recipes for disaster : an anarchist cookbook : a moveable feast. - CrimethInc. Ex-Workers' Collective (Salem, Oregon : Crimethinc Workers' Collective, 2012)
"Three years in the making, Recipes for Disaster is the long-awaited follow-up to the CrimethInc. collectives notorious first book, Days of War, Nights of Love. This 400-page manual complements the romance and idealism of that earlier work with practical information and instruction. Over thirty collectives collaborated in testing, composing, and editing the books 62 sections, which range from Affinity Groups, Coalition Building, and Mental Health to Sabotage, Squatting, and Wheatpasting. These are illustrated with extensive technical diagrams and first-hand accounts, and prefaced with a thorough discussion of the diverse roles direct action can play in social transformation. If youre looking for a tactical handbook for revolutionary action, look no further." -- Publisher's website
Includes bibliographical references (page 393) and index.
Keywords: Anarchism -- United States; Radicalism -- United States; Social change -- United States; Anarchism; Radicalism; Social change; United States